Rural Republican realignment in the modern South : the untold story - Hood, M. V.; McKee, Seth Charles, 1974- (University of South Carolina Press, 2022)
"Throughout the modern South many of the region's cities have become blue Democratic enclaves surrounded by crimson suburbs, and burgundy rural communities staunchly aligned with the Republican Party. This is almost a complete reversal of the pattern that existed for much of the twentieth century, during which the backbone of southern Democracy was located in rural counties. Now rural counties are the bulwark of modern southern Republicanism. What happened, and when? Those are the key questions that political scientists M. V. Hood III and Seth McKee explore in this pathbreaking study of rural Republican political realignment in the modern South. Understanding voting patterns in the rural South, and indeed in rural America more generally, has become central to understanding our current electoral landscape. In this empiracally-based study, Hood and McKee trace the shifting political affiliations in the rural South, arguing that this transition has been both more recent and more durable than most political observers realize. Whereas much of the literature on political realignment in the South has focused on urban/suburban voters, Hood and McKee set their sites on rural voters. They mine a variety of data sources to uncover granular detail about voting behavior in rural counties. They also conducted their own region-wide poll of rural voters, administered through the University of Georgia's School and Public and International Affairs (SPIA) Survey Research Center, where co-author M.V. Hood serves as director. The inclusion of original polling research represents a significant contribution and also highlights the fact that the authors are uniquely situated to offer a detailed regional analysis of rural southern politics. "Rural Republican Realignment in the Modern South" represents an extremely timely contribution to both scholarly and popular discussions surrounding the importance of region and race within contemporary electoral politics. While much of the attention in the aftermath of the 2016 presidential election focused on rural white voters in the Upper Midwest, the southern states of Florida (R +1.2%) and North Carolina (R +3.8%) both ranked among the top ten states with the narrowest margins of victory during the presidential contest. In both places, rural voters helped to fuel Republican success. The results of the 2018 midterm elections and 2020 presidential race further emphasize the importance of the American South and the rural/urban electoral divide. The authors include analysis of the 2020 election cycle and the US Senate runoff elections in Georgia, which occurred in early 2021. They make a compelling case that understanding the longer-term shift in voter preference within the rural South will remain vital to understanding both regional and national electoral patterns moving forward. The latest incarnation of the Republican Party, they write, traces its most well-worn and thus entrenched paths back to the one-party Solid Democratic South, and this is evident in the profiles of rural white supporters. In contrast, there is really no regional predecessor to the modern southern Democratic Party. Its fundamental elements are a diverse group of supporters who in the Old South would almost all have been disfranchised, played only a limited political role, or not resided in the region at all. This coalition includes northern in-migrants, African Americans, women, a growing Latino and Asian population, and a host of young people. While scholars are increasingly focusing on the changing South and how in many parts of the region high-growth urban areas are fostering Democratic competitiveness, Hood and McKee instead focus on the reason why Republicans have become so politically formidable and why the strong GOP affiliation of rural whites makes Democratic efforts to become a more viable opposition a generally slow and painstaking process. Put differently, they emphasize how partisan changes within the native white population in the South have proven capable of prolonging Republican electoral dominance as Republicanism has begun to wane among urban whites and is admittedly under siege among in-migrants to the Sunbelt"--